2016
DOI: 10.9775/kvfd.2016.15714
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoksin-Bağlayıcı Lokal Sodyum Bentonitin’in Yumurtacı Tavukların Üretim Performansı Üzerine Etkileri

Abstract: The study was designed to examine the effect of sodium bentonite (SB) as mycotoxin binder in poultry feed and its effects on productions performance of laying hens. A total of forty-five production hens white leghorn aged 34 weeks were caged in a naturally aired laying house into five different groups. Group A was kept as control group, Group B was fed with higher level 170 ppb aflatoxin without binders, and Group C feed contained 170 ppb aflatoxin with 1.5% SB binder, Group D contained 170 ppb aflatoxin with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The anti-mycotoxin additives (bentonite, kaolin, and activated charcoal) added to AFB1-contaminated feed had a positive effect in reducing the negative effects of AFB1 on the relative weights of the organs, as they act as substances that absorb toxins by intestinal villi. This indicates that the additives played a positive role in preserving liver cells from damage due to their content of binding substances [19,20]. These results are consistent with a study conducted by Lemos et al [21], which found that adding kaolin to chicken feed increased the intestinal villi (the duodenum) in broiler chickens, reducing the moisture content of the feces and thus improving the intestinal health of broiler chickens.…”
Section: The Effect Of Adding Clay Minerals and Activated Charcoal On...supporting
confidence: 88%
See 1 more Smart Citation
“…The anti-mycotoxin additives (bentonite, kaolin, and activated charcoal) added to AFB1-contaminated feed had a positive effect in reducing the negative effects of AFB1 on the relative weights of the organs, as they act as substances that absorb toxins by intestinal villi. This indicates that the additives played a positive role in preserving liver cells from damage due to their content of binding substances [19,20]. These results are consistent with a study conducted by Lemos et al [21], which found that adding kaolin to chicken feed increased the intestinal villi (the duodenum) in broiler chickens, reducing the moisture content of the feces and thus improving the intestinal health of broiler chickens.…”
Section: The Effect Of Adding Clay Minerals and Activated Charcoal On...supporting
confidence: 88%
“…In a study by Ghazalah et al [9], the addition of bentonite to broiler feed enhanced growth and reduced the negative effects of AFB1, showing the highest percentage increase in body weight compared to other treatments during the 29-30 day period. In another study, the addition of kaolin clay to feed at a ratio of (10,20,30) grams per kilogram of feed showed a significant improvement in feed intake and consequently improved growth [10]. A study conducted by Hu et al [11] found that adding montmorillonite clay to chicken feed positively increased weight.…”
Section: Effect Of Adding Clay Mineral and Activated Charcoal On Aver...mentioning
confidence: 99%
“…In agreement, [23] , found no significant effect on feed intake, weight gain and feed conversion rate. Researchers who used higher levels of AFB1 (500 ppb and 170 ppb) in poultry diets still observed no decrease on the weight and feed intake [11,15] . The insignificant AFB1 effect on feed intake could be explained by the fact that aflatoxins normally reduce energy availability which results to birds consuming more feed to meet their energy requirements [23] .…”
Section: Effects Of Aflatoxins On the Performance Of Broilersmentioning
confidence: 99%
“…A slurry was prepared by adding 10 ml PBS (pH 7.2) and then autoclaved. To 10 ml of the feed slurry, the aflatoxin working solution was added to obtain a concentration of about 40 µg/L [49], that is, 400 µL of 1 µg/ml aflatoxin working solution. To ensure proper distribution, small amounts of the feed slurry were continuously mixed with the Aflatoxin working solution and homogenised.…”
Section: Preparation Of Aflatoxin Spiked Feeds and Non-spiked Feedsmentioning
confidence: 99%